2022
DOI: 10.1021/acs.jpcb.2c05676
|View full text |Cite
|
Sign up to set email alerts
|

Time-Evolving Quantum Superpositions in Open Systems and the Rich Content of Coherence Maps

Abstract: We discuss the general features of the time-evolving reduced density matrix (RDM) of multistate systems coupled to dissipative environments and show that many important aspects of the dynamics are visualized effectively and transparently through coherence maps, defined as snapshots of the real and imaginary components of the RDM on the square grid of system sites. In particular, the spread, signs, and shapes of the coherence maps collectively characterize the state of the system and the nature of the dynamics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In this Letter, we supplement our earlier findings with an analysis of the excitation energy transfer (EET) pathways based on coherence maps . A coherence map (C-map) is a pair of snapshots that depict the real and imaginary parts of the system’s reduced density matrix (RDM) ρ ̃( t ) on the square grid of system states at a particular time t .…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In this Letter, we supplement our earlier findings with an analysis of the excitation energy transfer (EET) pathways based on coherence maps . A coherence map (C-map) is a pair of snapshots that depict the real and imaginary parts of the system’s reduced density matrix (RDM) ρ ̃( t ) on the square grid of system states at a particular time t .…”
mentioning
confidence: 83%
“…45 In this Letter, we supplement our earlier findings with an analysis of the excitation energy transfer (EET) pathways based on coherence maps. 49 A coherence map (C-map) is a pair of snapshots that depict the real and imaginary parts of the system's reduced density matrix (RDM) ρ(t) on the square grid of system states at a particular time t. The temporal evolution of the C-map offers a very effective visualization of a dynamical process in a multistate system because the magnitude and distribution of real and imaginary components encodes a wealth of dynamical information: 49 Further, when the coupling to the environment is diagonal in the basis of system states, as in the case of the Frenkel-type exciton−vibration Hamiltonian, 50,51 the time evolution of site populations is completely determined by the imaginary components of off-diagonal RDM elements weighted by state-to-state electronic couplings H jk e according to the relations 52…”
mentioning
confidence: 99%
“…The usual practice is to focus the numerical studies on the evolution of the population in the excited states of each of the chromophores. Here, we additionally use the recently developed coherencebased analytic techniques [43][44][45][46] to unravel the pathways that the excitation takes and the impact of the vibrational modes. Baker and Habershon [47] have explored these pathways in FMO using the Lindblad master equation.…”
mentioning
confidence: 99%
“…Wu et al [43] have built flux networks to analyze the flows along different pathways. More recently, Dani and Makri have shown that the time-derivative of the on-site populations is related to linear combinations of the off-diagonal terms of the reduced density matrix [44], and visualized the coherences in forms of maps that encode information about the dynamics of the system [45]. We extended these ideas to partition the time-dependent population change on a site in terms of transport along different state-to-state channels, which is useful for understanding the instantaneous population transfer in these systems with complex interconnects [46].…”
mentioning
confidence: 99%
See 1 more Smart Citation